Chronic Complications of Diabetes Mellitus: A Mini Review - Lotfy, Mohamed; Adeghate, Jennifer; Kalasz, Huba; Singh, Jaipaul; Adeghate, Ernest (Current Diabetes Reviews, 2017)
Introduction: Diabetes mellitus (DM) is a major metabolic disorder currently affecting over 350 million people worldwide. Also, another one billion people in the world are pre-diabetic, who may eventually end up with full- blown diabetes. It costs around 1,200 billion USD to diagnose, treat and care for both type 1 DM (T1DM) and type 2 DM (T2DM) patients globally. The disorder is rapidly increasing out of proportion in both developed and developing countries, especially T2DM, which is associated with modern lifestyle habits such as reduced physical activity, diet, obesity and genetic factors. If left untreated, DM can lead to a number of diseases and long-term complications leading subsequently to death. Areas Covered: In this mini review, we aim to highlight a number of complications, cascades or pathways (polyol, hexosamine, protein kinase C, advanced glycation-end product) of events and cellular, sub-cellular and molecular mechanisms associated with DM-induced hyperglycaemia (HG). Conclusion: Chronic complications of DM are caused largely by HG-induced cellular and molecular impairment of neural and vascular structure and function. HG-induced oxidative stress is a major contributor in the development of long-term complications of DM. DM-induced neuropathy and angiopathy, in turn, may lead to the dysfunction of cells, tissues and organ systems.
Keywords: Diabetes mellitus